A Methodological Review of Meditation Research - Thomas, John W.; Cohen, Marc (Frontiers in Psychiatry, 2014)
Despite over 50 years of research into the states of consciousness induced by various meditation practices, no clear neurophysiological signatures of these states have been found. Much of this failure can be attributed to the narrow range of variables examined in most meditation studies, with the focus being restricted to a search for correlations between neurophysiological measures and particular practices, without documenting the content and context of these practices. We contend that more meaningful results can be obtained by expanding the methodological paradigm to include multiple domains including: the cultural setting (‘the place’), the life situation of the meditator (‘the person’), details of the particular meditation practice (‘the practice’), and the state of consciousness of the meditator (‘the phenomenology’). Inclusion of variables from all these domains will improve the ability to predict the psychophysiological variables (‘the psychophysiology’) associated with specific meditation states and thus explore the mysteries of human consciousness.